Moriscos between the Franks and the Slowed down Islamic Support (897-1018 AH/ 1492-1609AD) - Khalaf Owaid, Firas Hamad (Journal of Tikrit University for Humanities, 2024)
The period of 897AH/1492AD to the year 975AH/1568AD in which Granada fell the last Muslim stronghold in Andalusia, with Christians was a period of bitter agony for the Muslims of Andalusia in general and Granada in particular, after the inquisition had violated all human values and took the rights of Muslims in envious spirit and disinterested of any compassion or humanity to the extent that it would not have been satisfied to live under the rule of Christians except to declare them innocent of the religion of Islam and to convert to Christianity and call them "Morskine”. Therefore, the Muslims of Granada did not stand idly by in front of the arrogance and brutality of the Inquisition, and after they were stranded in order to change their bitter reality, they declared their grand revolution in 975/1568 AD, which is also called the skin revolution, relative to the series of mountains around Granada, which barricaded the rest of the Muslims in which they declared their revolution. The revolution lasted for two years. It witnessed various forms of sacrifice. It represented the Islamic Championship against the oppression of the Christians and the Catholic Church, the notorious Inquisition. But that massive revolution was not successful for many reasons, including the fact that it has not received the assistance of States.